2021
DOI: 10.1097/prs.0000000000007776
|View full text |Cite
|
Sign up to set email alerts
|

Conformity of the Virtual Surgical Plan to the Actual Result Comparing Five Craniofacial Procedure Types

Abstract: irtual surgical planning and three-dimensional analysis are powerful tools in craniofacial surgery. Initial analysis provides a unique three-dimensional view of the anatomy, to help understand the preoperative dysmorphology. Virtual surgical planning also involves a digital "run-through" of the skeletal movements, allowing surgeons to spend time optimizing the treatment strategy preoperatively. The exact manner in which virtual surgical planning is used depends on the procedure type and goals of surgery. [1][2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The internal distractor vector control is a major concern in DO (14). The effect of virtual surgical planning (VSP) combined with CAD/CAM splints has been demonstrated in several studies (15)(16)(17). However, the virtual footplates could not be contoured to conform to the 3D models, and the requirement of strong 3D visualization capabilities increased the difficulty of establishing the required vectors of movement during the VSP procedure (Figure 7) (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The internal distractor vector control is a major concern in DO (14). The effect of virtual surgical planning (VSP) combined with CAD/CAM splints has been demonstrated in several studies (15)(16)(17). However, the virtual footplates could not be contoured to conform to the 3D models, and the requirement of strong 3D visualization capabilities increased the difficulty of establishing the required vectors of movement during the VSP procedure (Figure 7) (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the advantages of using stereolithographic models are an increase in surgical prediction reliability, improvements in the efficiency and precision of the procedure, reduction in surgical times and increases in patient safety. [6][7][8] Additionally, it favors the learning process of medical students and residents, as well as the education of both the patient and the family about their clinical condition and what is planned to be done. 2,4 As well as the education of not only the patient but also the family about the patient's clinical condition and the surgical plan.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, custom pre molded plates and personalized anatomical implants can be manufactured, making surgical planning a less tedious process and more in line with the reconstructive objective; in addition, it offers a guide for an adequate intraoperative execution, obtaining functional results with technical precision and aesthetic contour. 3 We present a case series of patients who underwent virtual planning and printing of stereolithographic models at the Hospital Militar Central, in Bogota, Colombia. success.…”
Section: Introductionmentioning
confidence: 99%
“…Almost two decades of research comparing traditional planning and VSP in terms of accuracy, time, and cost have been reported. [8][9][10][11] Patient-reported outcomes data comparing conventional 2D and 3D modeling demonstrate at least equivalent satisfaction between the two techniques by 4 months postsurgery. 12 In a systematic review, Nilsson et al reported that the computer-assisted design demonstrated shorter surgical and ischemia times for maxillofacial reconstruction and decreased preoperative planning time for orthognathic surgery compared with traditional planning.…”
mentioning
confidence: 96%